2005
DOI: 10.1007/s11120-005-2441-z
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent Self-assembly of 31-epimerically Pure and Mixed Zinc Methyl Bacteriopheophorbides-d in an Aqueous THF Solution

Abstract: The self-aggregation process of 3(1)-epimerically pure and mixed zinc methyl bacteriopheophorbides-d (ZMBPhes-d) was examined by stopped-flow technique. A 33(v/v)% tetrahydrofuran (THF) - water solution of ZMBPhe-d was rapidly mixed with a 7(v/v)% THF - water solution to form a chlorosome-type aggregate with a red-shifted Qy band around 700 nm. We observed a rapid autocatalytic aggregation in a subsecond time scale. Aggregates of the 3(1)R epimer increased with a change in the Qy absorption maximum from 698 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…It was previously reported that zinc methyl bacteriopheophorbide‐ d epimers 5 R/S stereoselectively self‐aggregated in 1% CH 2 Cl 2 and (cyclo)hexane as well as in an aqueous solution containing THF or α ‐lecithin to form supramolecular structures dependent on the 3 1 ‐chirality . In an aqueous TX‐100 micelle solution, (3 1 R ) ‐ epimer 5 R afforded broadened and redshifted electronic absorption bands at 708 and 434 nm, compared with the monomeric bands (648 and 422 nm in THF), where large exciton‐coupled CD couplets were observed (red line of Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It was previously reported that zinc methyl bacteriopheophorbide‐ d epimers 5 R/S stereoselectively self‐aggregated in 1% CH 2 Cl 2 and (cyclo)hexane as well as in an aqueous solution containing THF or α ‐lecithin to form supramolecular structures dependent on the 3 1 ‐chirality . In an aqueous TX‐100 micelle solution, (3 1 R ) ‐ epimer 5 R afforded broadened and redshifted electronic absorption bands at 708 and 434 nm, compared with the monomeric bands (648 and 422 nm in THF), where large exciton‐coupled CD couplets were observed (red line of Fig.…”
Section: Resultsmentioning
confidence: 97%
“…700 nm (1% CH 2 Cl 2 −cyclohexane) . In addition, its self‐aggregation has been studied in an aqueous solution containing THF, α ‐lecithin or Triton X‐100 (TX‐100) . Its 3 1 ‐epimerically pure 5 R and 5 S showed different self‐aggregation behavior in these solutions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, time-dependent spectroscopic changes, in emission intensity, shift of maximal emission wavelength, or absorbance, have been observed for compounds that undergo self-assembly in solution (Gassensmith et al, 2007;Miyatake et al, 2005). Taken together, these observations suggest that BODIPY 2b shows a tendency to form assembled structures in The molecular structure of the title compound, with displacement ellipsoids drawn at the 30% probabilty level.…”
Section: Solvent-dependent Behaviour Of Bodipy 2b Observed By Nmr Spementioning
confidence: 93%
“…Diastereomeric control by the 3 1 -epimers in 1 R and 1 S has been well studied: the stereochemical difference at the 3 1 -chiral center in 1 greatly influenced their self-aggregation behaviors (Figure S3, Supporting Information). ,, We examined self-aggregation of 3 R and 3 S and found a similar diastereomeric control by the 3 1 -configuration (Figure S3, Supporting Information). A common feature in 1 and 3 was that the UV−vis spectrum of each 3 1 R form in the self-aggregates was similar to that of the corresponding diastereomeric mixture (Figure ).…”
mentioning
confidence: 71%